MODEL MEMBANGUN DESA MANDIRI - Harjo, Budi (Universitas Sang Bumi Ruwa Jurai, 2017)
The village as an entity that until now still lagging behind in development has received great attention from various circles, both the government itself and the Non-Governmental Organization and Higher Education. But building up the village that has been done with the assumption that